Hyers-Ulam Stability for a Class of Quadratic Functional Equations via a Typical Form - Chang Il Kim; Giljun Han; Seong-A. Shim (Abstract and Applied Analysis)
We investigate the following typical form of a certain class of quadratic functional equations: . Furthermore, we provide a systematic program to prove the generalized Hyers-Ulam stability for the class of functional equations via the stability for the typical form.